STUDI INTERAKSI OBAT-OBAT JANTUNG YANG DILAKUKAN TERHADAP ORANG SEHAT: TINJAUAN SISTEMATIS - Sumartin, Yunita; Sukandar, Elin Yulinah (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
Patients with cardiovascular disease have a higher prevalence of drug interactions than other patient groups. Drug interactions may result from pharmacokinetic or pharmacodynamic mechanisms. This study is a systematic review that aims to identify drug interactions related to cardiac drugs. Article searches were conducted on PubMed and ScienceDirect databases to identify all articles on cardiac drug-drug interaction studies. The search started from articles published in 2013 to 2023. The keywords used in the article search were as follows: drug-drug interactions, cardiac patient, cardiac drug, cardiovascular drug, pharmacokinetics interaction, pharmacodynamic interaction combined with the boolean operator